KITAB WAHYU DALAM GEREJA KATOLIK : Sebuah Proses Memaknai Pengharapan - Wilson, Gregorius (Jurnal Alternatif Wacana Ilmiah Interkultural, 2023)
The Book of Revelation is the last book in the Bible. Bible readers (especially Catholics) have very few opportunities to read the Book of Revelation because it does not have much of a place in the Church's Liturgical calendar. The spread of information about the interpretation of the Book of Revelation which leads to predictions of the end times makes people anxious and afraid. In fact, since Jesus died on the Cross, until now, there has never been an end time. The research method used in writing this paper is a library research method by comparing several previous studies to find answers to problems of understanding of the people. The library research method can provide an explanation of the history, culture and background of the Book of Revelation so that readers and people today understand the theological message and reflect it in their lives. The way contemporary people understand the Book of Revelation needs to be renewed with a perspective of hope, so that the text of the Book of Revelation can be reflected in a new way. Hope is one of the three Christian virtues, faith, hope, and love. Hope plays an important role in reflecting on the suffering and difficulties of life. Humans who have hope will interpret suffering as part of their spiritual journey to unite with their Father in Heaven. The Christian people in Asia Minor is described in the Book of Revelation as a congregation that struggled to maintain its faith in the midst of suffering. The text of the Book of Revelation invites readers today to have hope in God's promises, and believe that God will fulfill His promises in the future as described in the prologue and epilogue of the Book of Revelation. Kitab Wahyu merupakan Kitab terakhir dalam Alkitab. Pembaca Alkitab (khususnya Umat Katolik) sangat sedikit mendapat kesempatan membaca Kitab Wahyu karena tidak banyak mendapat tempat dalam penaggalan Liturgi Gereja. Persebaran informasi tentang tafsir Kitab Wahyu yang mengarah pada prediksi akhir zaman membuat masyarakat resah dan ketakutan. Padahal sejak Yesus Wafat di Salib, sampai dengan saat ini, belum pernah terjadi akhir zaman. Metode penelitian yang digunakan dalam penulisan makalah ini adalah metode penelitian pustaka dengan membandingkan beberapa penelitian terdahulu untuk menemukan jawaban atas persoalan pemahaman umat. Metode penelitian pustaka dapat memberikan pemaparan sejarah, budaya, dan latar belakang Kitab Wahyu sehingga pembaca dan umat saat ini menangkap pesan teologis dan merefleksikannya dalam kehidupan. Cara jemaat masa kini memahami Kitab Wahyu perlu diperbarui dengan persepktif pengharapan, sehingga teks Kitab Wahyu dapat direfleksikan secara baru. Pengharapan adalah salah satu dari tiga kebajikan Kristiani, iman, harapan, dan kasih. Harapan berperan penting dalam merefleksikan penderitaan dan kesulitan hidup. Manusia yang berpengharapan akan memaknai penderitaan sebagai bagian dari perjalanan rohani untuk bersatu dengan Bapa di Surga. Jemaat Kristen di Asia Kecil, digambarkan dalam Kitab Wahyu sebagai jemaat yang berjuang untuk mempertahankan imannya di tengah penderitaan. Teks Kitab Wahyu mengajak pembaca saat ini untuk berpengharapan pada janji Allah, dan percaya bahwa Allah akan menggenapi janji-Nya pada saatnya kelak seperti yang digambarkan dalam prolog dan epilog dari Kitab Wahyu.